Exploring Students' Difficulties in Answering Reading TOEFL Section Test - Wahyuningsih, Citra; Mahbub, Moh. Arif; Al Fauzi, Fatih (Linguapedia, 2024)
Test of English Foreign Language (TOEFL) is widely used as a measurement for standardized English competencies. This study attempted to explore EFL learners' difficulties in dealing question of reading section in TOEFL test. Qualitative case study research design and semi-structured interview as instrument to gain the data. In this study with four participants were purposively selected from the English Education Department of Private University of Jember who has passed the TOEFL test. The findings revealed that there were two factors that become difficulties or obstacle faced by the TOEFL test-takers in completing TOEFL reading questions. First, the factor that is caused from several kind of questions that are difficult to answer for the participants, including; unstated detail question, implied detail question, and vocabulary in context question. Second, the factor that is caused by each participant personally, including ; lack of mastering vocabulary, limitation of time, and unfamiliar vocabularies. The result of this study are expected to have practical contribution on determining the appropriate strategies employed to minimize students' error during answering the TOEFL test.